Excess of Loss Reinsurance: Review of standard clauses: (Fire and Allied Perils) - Pearce, Eric A. (Assurances)

(untitled) (HEC Montréal, 1973)
The standard clauses in use at the present time in some contracts of Excess of Loss Reinsurance are being reviewed here. My remarks are, in general, based on contracts for Fire and Allied Perils and the subject matter must of necessity be open to criticism. Indeed, I hope that friends in the field of reinsurance, be they ceding Companies, Reinsurers or Brokers, will draw attention to any points which in their view are incorrect, liable to misinterpretation or could be more happily expressed. A reinsurance comes into being as the result of negotiations between the parties. The negotiations may be brief or, on the contrary, very long drawn out, but always without exception the negotiations are treated with the utmost seriousness in an endeavour to equate the requirements of the Company with the protection which the Reinsurer is able and willing to offer. When agreement has been reached, it is customary (in some countries it is a legal requirement) for the terms agreed upon to be embodied in a written contract. Thus, any point which has been discussed between the parties during negotiations would be expected to find its place in the written contract. It is surprising that one or even bath the parties will be satisfied with a document which does not, in detail, express the intentions hammered out and agreed upon during negotiations. Of course, if serious disagreement should arise, recourse will be had to relevant correspondence, notes of conversations or the understanding of the intermediary at the time, and usually some sort of compromise is reached. But why should that sort of difficulty arise, when a few hours of study and consideration of the draft contract would lead to further exchange of views and avoidance of ambiguity. The answer to that question is that quite often one party will believe that the draft being considered has the authority of a standard policy form, such as is used for Fire, Accident or other recognised class of insurance. This is not necessarily the case. Usually the draft contract is prepared by the Reinsurer or Broker acting in good faith. There will be clauses which have stood the test of time and which the Reinsurer would be reluctant to change and other clauses may be quite optional and expressed in a particular form of words because it is what the person drafting the contract understood to be the intention expressed during negotiations. ln either case a much healthier and happier atmosphere exists if points of difference are discussed before a controversial claim arises. So, my endeavour in the notes set out below is to draw attention to matters which seem to me to be important and might give rise to disappointment if not fully understood by both parties at the time of signature of the contract. It will be seen that I have avoided any comments on the situation which might arise in the event of a Company going into liquidation. ln such difficult circumstances, the judiciary in the particular country may be expected to direct the manner in which any question is to be resolved.